Memahami Filsafat Postmodernisme Jean Francois Lyotard: Studi Pemikiran Francois Lyotard tentang Postmodernisme - Aritonang, Michael Ricardo (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2024)
The emergence of postmodernism provides a signal for the modern era regarding the emergence of criticism and constructive and destructive efforts towards thinking that developed in the modern era. Of course, the criticism that arises is part of the concerns of philosophers according to their own paradigm. Jean Francois Lyotard was a poststructuralist philosopher, but he later became better known as one of the important thinkers of the postmodernist philosophical school who was famous for his idea of ​​rejecting the Grand Narrative, namely a big story that has a legitimating function because it is unifying, universal and total. Rejection of grand narratives, according to Lyotard, means rejection of unification, universality and totality. In the view of Lyotard, this is one of the most prominent distinguishing characteristics between the philosophy of postmodernism and the philosophy of modernism. Postmodernism is a reform theory that understands belief in relative truth, an understanding that rejects assumptions about reality, truth, and universalist thinking about knowledge that continues to expand about the human world.